Jarimah Al-Riddah from the Perspective of Islamic Law and its Relevance in the Legal System in Indonesia - Sri Rizki Wardani; Humaira Hananni Harahap (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
This study aims to analyze the concept of jarimah al-riddah from the perspective of Islamic criminal law and examine its relevance in the Indonesian legal system. Jarimah al-riddah is understood as an act of leaving the Islamic religion which in classical Islamic criminal law is categorized as a criminal act with certain sanction consequences. This study uses a normative legal research method with a statutory and conceptual approach, through a study of Islamic legal sources and applicable laws and regulations in Indonesia. The results of the study indicate that there are differences of opinion among scholars regarding the application of sanctions against perpetrators of riddah, especially in the context of modern society. On the other hand, the Indonesian legal system does not explicitly regulate jarimah al-riddah as a criminal offense, but rather emphasizes the protection of religious freedom as guaranteed in the constitution. Therefore, the application of the concept of jarimah al-riddah in the Indonesian context requires a contextual approach that takes into account human rights values and the principle of legal pluralism.